2018
DOI: 10.2196/11083
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Secondary Stroke Prevention Initiative Design: Study Protocol and Rationale for a Randomized Controlled Trial

Abstract: BackgroundHispanic-Latino populations face a disproportionate stroke burden and are less likely to have sufficient control over stroke risk factors in comparison with other ethnic populations. A promising approach to improving chronic health outcomes has been the use of community health workers (CHWs).ObjectiveThe objective of this randomized controlled trial is to evaluate the effectiveness of a CHW intervention among Latino patients at risk of recurrent stroke.MethodsThe Hispanic Secondary Stroke Prevention … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…17,18,20,21,31 The risk factor "dyslipidemia" was considered in some articles. 11,12,16,23,27,29 Finally, Connected Health Interventions to Cardiovascular Disease Prevention Agher et al…”
Section: Risk Factors For Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18,20,21,31 The risk factor "dyslipidemia" was considered in some articles. 11,12,16,23,27,29 Finally, Connected Health Interventions to Cardiovascular Disease Prevention Agher et al…”
Section: Risk Factors For Cardiovascular Diseasesmentioning
confidence: 99%
“…The patients with cardiometabolic disease studied reported that lifestyle-targeting text messaging approaches were feasible and acceptable, and that the text messages were easy to understand (88%) and were sent at an Connected Health Interventions to Cardiovascular Disease Prevention Agher et al 549 appropriate frequency (71%), in appropriate language (88%). Most of the studies used "smartphone health applications (connect)" [8][9][10][11][12]15,16,19,20,22,[24][25][26][27] . "Focus group" (do) and "Education" (read) were used together in two articles.…”
Section: Connected Health Interventionmentioning
confidence: 99%